Ubuntu philosophy as a strategy to promote access to under-five child healthcare services - Livhuwani Tshivhase; Idah Moyo (Curationis)
Background: Inaccessibility of healthcare services for children under five contributes to child morbidity and mortality in sub-Saharan Africa. Children are reportedly dying at home from treatable conditions, hence the need for this study.